2016
DOI: 10.2147/opth.s119251
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of the relationship between serum lutein and zeaxanthin levels and macular pigment optical density

Abstract: PurposeTo assess the relationship between combined serum lutein and zeaxanthin (L+Z) concentration and macular pigment optical density (MPOD), and to investigate the effect of L+Z+docosahexaenoic acid (DHA) dietary supplementation on the spatial distribution of MPOD.MethodsTwenty healthy fellow eyes with unilateral wet age-related macular degeneration or chronic central serous chorioretinopathy were included. All participants received a dietary supplement for 6 months that contained 20 mg L, 1 mg Z, and 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…However, the results from this study show stronger correlations between serum carotenoid concentrations and MPOV than previously reported using subjective methods (nonimaging-based systems) and for imaging techniques reporting only at a single eccentricity 41. The current finding is consistent with other studies,42 as confirmed by Conrady et al,33 also using the Spectralis MPOD module, where serum carotenoid concentrations showed a stronger correlation when a broader area of MP was assessed and reported. As expected, in our study MPOV exhibited a strong correlation with MPOD at all eccentricities; however, the strength of the agreement increased with increasing eccentricity.…”
Section: Discussionsupporting
confidence: 90%
“…However, the results from this study show stronger correlations between serum carotenoid concentrations and MPOV than previously reported using subjective methods (nonimaging-based systems) and for imaging techniques reporting only at a single eccentricity 41. The current finding is consistent with other studies,42 as confirmed by Conrady et al,33 also using the Spectralis MPOD module, where serum carotenoid concentrations showed a stronger correlation when a broader area of MP was assessed and reported. As expected, in our study MPOV exhibited a strong correlation with MPOD at all eccentricities; however, the strength of the agreement increased with increasing eccentricity.…”
Section: Discussionsupporting
confidence: 90%
“…Since lutein must be obtained from the diet, principally from leafy green vegetables, fruits, and egg yolk [19], researchers have explored whether dietary supplementation with lutein might prevent AMD in healthy people or improve the condition of patients with AMD. Several studies support these possibilities [15, 20, 21] and have demonstrated that lutein supplementation can improve visual acuity [22]. On the other hand, one study showed that supplementation did not significantly improve MPOD in patients with early AMD [23].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Skin Raman requires specialized equipment and cannot readily distinguish between the various carotenoids, but it is rapid, painless, and correlates well with HPLC total serum and biopsied tissue concentrations, and moderately well with dietary surveys. 13 , 14 Unfortunately, serum and skin carotenoid measurements have not correlated particularly well with assessments of ocular carotenoid status ( Tables 1 , 2 ), 15 – 28 and dietary correlations have fared even worse. In the published literature, although these correlations with macular pigment may be statistically significant, the r values are typically very low.…”
mentioning
confidence: 99%